2020
DOI: 10.2147/ijn.s243223
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nanoparticle Drug Delivery System for Glioma and Its Efficacy Improvement Strategies: A Comprehensive Review</p>

Abstract: Gliomas are the most common tumor of the central nervous system. However, the presence of the brain barrier blocks the effective delivery of drugs and leads to the treatment failure of various drugs. The development of a nanoparticle drug delivery system (NDDS) can solve this problem. In this review, we summarized the brain barrier (including bloodbrain barrier (BBB), blood-brain tumor barriers (BBTB), brain-cerebrospinal fluid barrier (BCB), and nose-to-brain barrier), NDDS of glioma (such as passive targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 164 publications
0
82
0
Order By: Relevance
“…Brain distribution can be facilitated by nanotechnology [ 150 ]. Studies have shown that nanotherapeutics and nanomaterials improve the biodistribution of drugs in the brain for more efficient treatment of glioblastoma, not only via convection-enhanced delivery [ 151 ] but also via intranasal delivery [ 152 ].…”
Section: Current Status Of Approved Drugs For Nasal Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain distribution can be facilitated by nanotechnology [ 150 ]. Studies have shown that nanotherapeutics and nanomaterials improve the biodistribution of drugs in the brain for more efficient treatment of glioblastoma, not only via convection-enhanced delivery [ 151 ] but also via intranasal delivery [ 152 ].…”
Section: Current Status Of Approved Drugs For Nasal Applicationmentioning
confidence: 99%
“…Chemotherapeutic agents are in general considered for INDD systems [152,153]. The main advantage of the IN route is the chance of reduced side effects in other organ systems [146,154].…”
Section: Intranasal Application Used For Cns Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to selectively act drugs on the lesions and reduce the impact on peripheral tissues, a brain drug delivery system needs to be established. Osmotic BBB disruption based on intra-arterial infusion of hypertonic mannitol solution, intravenous bradykinin analogs that relax tight junctions, drugs coupling to a mediator targeting and shuttling insulin or transferrin receptors, nanoparticle drug delivery system, and direct delivery of drugs to the brain parenchyma or excision cavity are potential methods for metabolic immunotherapeutic drugs to cross BBTB ( van Tellingen et al, 2015 ; Li et al, 2020 ). Targeting metabolic functional proteins selectively and highly expressed in glioma cells, such as GLUT3 ( Xu et al, 2015 ; Zheng et al, 2016 ), or using targeted metabolic drug delivery systems based on neutrophils ( Osuka and Van Meir, 2017 ; Xue et al, 2017 ) or other immune cells accumulating in glioma tissues is also a good solution.…”
Section: Discussionmentioning
confidence: 99%
“…This strictly limited selection imposes a great challenge on glioma treatment. To overcome this issue, various nanoparticulate platforms have been widely investigated to develop BBB-penetrating delivery systems because of their great clinical potential in cancer diagnosis and treatment [4][5][6]. These nanoplatforms can be exploited as imaging agents to guide the maximal surgical resection, drug carriers to improve chemotherapy, or theranostic systems to achieve imaging-guided drug delivery and therapy monitoring [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%